Agricultural biogas plants in Poland – selected technological, market and environmental aspects. (May 2016) - Piwowar, Arkadiusz; Dzikuć, Maciej; Adamczyk, Janusz
Abstract: Renewable energy plays an increasingly crucial role in ensuring the energy security of Poland. Due to a large area of agricultural land, a relatively high cattle and pig population, and well-developed agri-food industry, the main source of renewable energy in Poland is agricultural biomass. The study focuses on the development of agricultural biogas production in Poland. The main purpose of the considerations was to present the current state of development of the agricultural biogas market in Poland, including technological aspects. As it appears from the analyses, the production of agricultural biogas increased in 2011–2014 by 137.29 million m 3 . Also the structure of consumption of substrates from the agricultural biogas production changed towards a wider use of products from the agri-food industry. Currently, the total capacity of plants for the production of agricultural biogas in Poland is 244, 156, 466 m 3 /year. The use of biogas from agricultural biogas plants is an increasingly important element of the distributed power generation in Poland.